(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Per- and polyfluoroalkyl substances (PFAS) are a diverse group of synthesized chemicals used in a wide range of consumer and industrial products. It consists of a group of more than 4700 chemical compounds for which the characteristic perfluorinated carbon moiety confers hydrophobic chemical properties and environmental persistence. Certain PFAS are also intentionally added as ingredients in some cosmetic products, including lotions, cleansers, nail polish, shaving cream, foundation, lipstick, eyeliner, eyeshadow, and mascara. These PFAS are used in cosmetics to conditioning and smooth the skin, making it appear shiny, or to affect product consistency and texture. Some common PFAS used as ingredients in cosmetics include PTFE (polytetrafluoroethylene), perfluorooctyl triethoxysilane, perfluorononyl dimethicone, perfluorodecalin, and perfluorohexane. These highly persistent and potentially toxic class of chemicals, are added to cosmetics to increase their durability and water resistance.